Urgent Geriatric Outpatient Clinic - Easy Access to Comprehensive Geriatric Assessment for Older Home-Dwelling Persons Living with Frailty - Jonna Laine; Marika Salminen; Laura Viikari; Tero Vahlberg; Paula Viikari; Hannele Tuori; Maarit Wuorela; Päivi Rautava; Matti Viitanen (TAIWAN SOC GERIATRIC EMERGENCY & CRITICAL CARE MEDICINE-TSGECM, 2022)
Background: Emergency departments (ED) are not designed to meet the complex medical and social needs of older people. An easy access Urgent Geriatric Outpatient Clinic (UrGeriC) was started in order to provide rapid and more appropriate care and assistance for frail older people struggling to manage at home.Methods: Participants were older Finnish home-dwelling citizens who had presented themselves in August 2015 to Turku City Hospital UrGeriC (n = 76) or ED of Turku University Hospital (n = 216) and who were discharged home.Results: UrGeriC patients were older (85.7 +/- 5.4) (mean age +/- SD) than ED patients (83.3 +/- 5.3) (p < .001). Compared to ED patients, UrGeriC patients were more often female (79% vs. 61%, p = .005) and living alone (67% vs. 52%, p = .025). The proportions of patients using home care (56% in UrGeriC vs. 30% in ED, p < .001) and having contact with health services within previous two weeks (62% vs. 46%, respectively, p = .005) were higher in UrGeriC than in ED. To ensure safe living at home, additional help was arranged for a greater proportion of patients presenting themselves to UrGeriC than to ED (32% vs. 3%, p > .001). No significant differences were found in staying at home four weeks (unadjusted OR 1.69 [95% CI 0.62-4.62], p = .305; adjusted 1.42 [0.50-4.01], p = .507) or one year (unadjusted 1.53 [0.69-3.41], p = .295; adjusted 1.51 [0.65-3.50], p = .339) after discharge between UrGeriC and ED patients.Conclusions: According to our preliminary results, UrGeriC could be a suitable way to support the home care of multimorbid geriatric patients struggling to live at home. Copyright (C) 2019, Taiwan Society of Geriatric Emergency & Critical Care Medicine.